Ways to increase the vegetable production in Romania - Diana Necula; Rozi Berevoianu; Dan Veverca; Eduard Dumitru (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Vegetable growing, as sector of horticulture, has a strategic role within the national economy, whereas vegetables is a component of great importance for the nutrition of the population. This work aims to identify ways to increase national production of vegetables in order to increase the average annual national consumption. Currently, the average consumption of fresh vegetables in the equivalent, in our country, is around 150 kg/capita. Ways to increase production of vegetables consist both in surface growth of vegetables in protected spaces and in the field and also the average yields per hectare, by improving technologies. We emphasize that these measures may result in the development of our country vegetable growing, increase employment of rural population and reducing imports of vegetables.
Keywords: 330; growing vegetables; production; consumption